KORELASI AKTIFITAS FISIK DENGAN KEJADIAN OBESITAS PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH PADANG - Yusti Siana; Yuri Haiga; Mhd Nurhuda; Dian Puspita; M. Syaikhan Azzamul Khair (Nusantara Hasana Journal, 2025)
Obesity is an excessive accumulation of fat in all body tissuesevenly which results in health problems and causes various diseases such as hypertension, diabetes, and heart attack. A person who is said to be obesity can be done by measuring the Body Mass Index (BMI). Lack of physical activity is oneof the factors that increase the risk of obesity. The intensity of physical activity performed will affect body weight, depending on the weight and lightness of the physical activity performed. The purpose of this study to discover the correlation physical activity towards occurrence of obesity in medical students of, Baiturrahmah University, Padang. This research involved the field of public health and internal medicine. This type of research is analytic correlation with cross sectional design. This research was conducted in March-December 2022 at the Faculty of Medicine, Baiturrahmah University Padang. The population in this research is medical students, Baiturrahmah University Padang with 29 samples. Data analysis is univariate displayed with frequency distribution tables and bivariate analysis by using chi-square test with SPSS version 23.0 program. The result of this research showed, the average age of students was 21.17 ± 0.85 years; weight 88.66 ± 10.14 kg ; height 164.66 ± 8.00 cm; as manyas 58.6% are woman, as manyas 69.0% are with moderate activity, 79.3% had obesity I, 73.9% are obesity I with moderate activity and there was no correlation between physical activity toward the occurrence of obesity in medical students, Baiturrahmah University Padang (p = 0.222). There is no correlation between physical activity toward occurrence of obesity in medical students, Baiturrahmah University Padang.